Transmigration as a Strategy for Strengthening National Food Security - Mas Wedar Haryagung Adji; Santi Yulianti; Syifaa Tresnaningrum; Erna Gustina Norrista (Pusbindiklatren Bappenas, 2021)
Indonesia is one of the largest agricultural countries in Southeast Asia, but it is also struggling with food security issues. The government's challenge is to ensure that domestic food needs are fulfilled. The covid-19 pandemic exacerbated this challenge, where countries faced the threat of food shortages due to limited movement of goods. Thus, Indonesia should focus on increasing the production and productivity of strategic food commodities. One of the alternative solutions is through the transmigration program. This research focused on how the transmigration program can contribute to food security. The study was carried out through a descriptive qualitative method. The result shows that transmigration contributes to food security because of its similarity to the food production process. However, this program faces five main challenges to support food security. Therefore, this study shows several pre-conditions that the government needs to fulfill to overcome these challenges.